Sistem Pendukung Keputusan Penentuan Penerima Bantuan Langsung Tunai Dana Desa (BLT-DD) Di Desa Banaran Kabupaten Sukoharjo Dengan Metode AHP (Analytical Hierarchy Process) dan SAW (Simple Additive Weighting) - Fitri Nur Azizah; Ika Pradipta Yuniawan (Redtech Putra Benua, 2024)
The Direct Cash Assistance (BLT) program from the Village Fund is a government initiative aimed at alleviating the economic hardships of vulnerable communities, particularly during emergencies. In Banaran Village, Sukoharjo Regency, selecting appropriate recipients for BLT-DD is crucial to ensure that the aid reaches those who are most in need, including low-income individuals and people with disabilities. However, the process of selecting recipients involves complex criteria, such as family status, the number of dependents, and whether the individual is already receiving other social assistance. This research proposes a Decision Support System (DSS) that integrates the Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) methods to determine the most eligible recipients of BLT-DD in Banaran Village. The AHP method is used to assign weights to various criteria, including family status (head of household, spouse, or child), the number of dependents, and current social assistance. The SAW method then ranks potential recipients based on these weighted criteria.